An exploratory study of cyberbullying among UTAR Kampar campus student - Goh, Alan Boon Yap; Leong, Khye Sum; Rahul Varma Prasaad, Segaran; How, Wai Kiat; Wong, Wai Shan (2018)
Cyberbullying is a topic that is worth to research, according to statistics, cyberbullying has become one of the important factors which lead to suicide cases among the university students in Malaysia. For instance, in year 2017, the main reason behind the death of a student from Tunku Abdul Rahman University College in Penang who committed suicide found to be cyberbullying. Cyberbullying is happening around the world not only in Malaysia. However, cyberbullying is taken seriously in USA. Almost 40% of the students in USA had been a victim of cyberbullying. The students have a very high suicidal rate because they could not bear the insult and humiliation by their schoolmates via social media. In this research, social cognitive theory will be applied. The findings and analysis will be determined using qualitative research method. Five focus group consisted of 50 participants from five different faculty which are FAS, FICT, FBF, FEGT and FSC of 50 participants in Universiti Tunku Abdul Rahman. In conclusion, we have exposed the common type of cyberbullying nowadays is harassment.